An Observational Study of the Effect of Concomitant Levetiracetam on Apixaban Concentrations in a Hospital Cohort - Chazmyn Riley; Kevin Lam; Cristina Micale; Lynda Thomson; Douglas F. Stickle; Walter K. Kraft (Clinical and Translational Science, 2026)
ABSTRACT Despite the lack of evidence of a mechanism‐based drug interaction, some professional organizations have advised caution coadministering apixaban and levetiracetam. Eligible patients taking apixaban with or without levetiracetam for any indication for at least 72 h were screened from the electronic medical records. Plasma samples from 77 patients were retrieved from salvaged clinical blood collections. Apixaban minimum and maximum concentrations ( C min and C max ) were compared using descriptive statistics in R. While the median C min and C max appear to be marginally elevated, there were no apparent differences relative to apixaban alone. These findings suggest no apparent interaction of levetiracetam and support the current lack of labeled warning of concomitant apixaban dosing.